Aleatoriedad geográfica en los cambios de precipitación de las series más largas de España - Manuel García, Conrado Miguel; Sanz Donaire, Juan José (M+A. Revista Electrónica de Medioambiente, 2006)
In the present paper several statistical essays are made to determine whether the positive values of annual rainfalls (bigger than the mean, as expressed in deviation) for 50 Spanish rain gauges are distributed in a random way. Different clusterings has been made: from a unique group to total desaggregation. Other groups were made according to geographical grids (latitude-longitude) in several spacing, and according to climatic regions. In any case results confirm spatial randomness.
Keywords: Rainfall; Spatial randomness; Spain